ANALISIS INVESTASI CHINA KE INDONESIA SEBELUM DAN SESUDAH ACFTA - Ragimun, Ragimun (Jurnal Kajian Ekonomi dan Keuangan, 2009)
Economic growth of China's stunning last decade to provide a map of this new world economic power. While in some parts of the world is experiencing stagnant growth, but this country is experiencing economic growth is high enough. This means to give new hope for many regions and countries that have economic relations with this country, not the exception of Indonesia. But this is also a concern our country and other countries, such as Asean. Therefore, the ASEAN China Free Trade Area (ACFTA), which is one of the regional agreement, have an important role in bridging the interests of Asean with China's economy, including Indonesia.For Indonesia, ACFTA has a positive effect because the Chinese clearly requires the supply of raw materials and auxiliary materials for industry, as well as market share and a quite promising partner. However, on the other hand, our country is ready to fight the flood of products from that country. There is no other way that can be adopted to avoid the economy unless they increase the can be obtained that the competitiveness products still need to be improved, especially competitiveness of our products.By using the SWOT analysis approach, the results through product manufacturing efficiency, while products such as pre-eminent natural resources still can be improved with the increase in value added. From the results of the analysis is also known that after ACFTA the investment of China is still relatively small.